Música e crítica social nas ditaduras da Argentina : a complexidade envolvendo a cena musical (1955-1983) - Santana, Mariana Aparecida de Oliveira (2022)
The present work aimed to make an analysis on the use of music as a social criticism in the context of three very remarkable dictatorships in the history of Argentina: the dictatorship of 1955-57, known as the “Liberating Revolution”, the dictatorship of 1966-73, known as the “Argentine Revolution” and the dictatorship of 1976-83, self-styled as the National Reorganization Process. To this end, a brief historical, political, economic and social overview of the Contemporary History of Argentina was presented. From there, an analysis was made of the musical productions whose lyrics were considered “not suitable” to be disseminated, according to the decree of law 4.161/56, which consisted of five articles that aimed to desperonizar Argentina through severe restrictions, such as the prohibition of images, symbols and expressions that were associated with Peronism and also a list of words: peronism, peronist, justicialismo, justicialist, third position, the acronym PP (referring to the Peronist Party), and the musical compositions called “ Los muchachos peronistas” and “Evita Capitana”, which became symbols of Peronist resistance; In the same way, an analysis was carried out of the musical productions that had their lyrics considered inappropriate according to the broadcasting law, nº 22.285/80, a law applied by COMFER (Federal Broadcasting Committee) - state censorship body managed by military and ecclesiastics. We also sought to analyze, from bibliographic surveys, what were the trends, the most popular musical styles in the three periods (tango, folk and rock), aiming to contribute to the set of studies on the subject, undertake a study of the different groups musicals that emerged in this period, and the existing musical groups that used music to denounce and fight against the system imposed by the dictatorial governments of those times. In this sense, because it is a research that used music as a historical source, the work was based on the studies of two authors who work this relationship between History and Music: Marcos Napolitano and José D' Assunção Barros.